Disparities in Funding for Public Services between Rural and Urban Villages - Muawanah; Ali Maskur (Universitas Serang Raya, 2026)
Funding gaps between Indonesia's desa and kelurahan have become a systemic barrier to the delivery of optimal public services. Villages are guaranteed Village Funds from the central state budget, while sub-districts rely entirely on constrained local budgets. This study analyzes the impact of this imbalance on public services in sub-districts and evaluates the legal effectiveness and fairness of Article 41 of Kendal Regent Regulation Number 60 of 2023 concerning Sub-district Community Institutions. Using a qualitative approach, this normative-empirical legal study gathered data through literature reviews and field observations in several sub-districts across Kendal Regency. The results show that the funding gap between villages and sub-districts is significant: villages receive billions of rupiah per year, whereas sub-district community institutions receive minimal or no allocations. This directly contributes to the stagnation of community institutions' activities, such as Posyandu, PKK, Karang Taruna, and Satlinmas, and to the deterioration of public facilities. Article 41 of the Kendal Regent Regulation is considered ineffective and does not meet the principles of justice because it is facultative (“can be sourced”) and contains the phrase “not binding,” thus failing to guarantee adequate and fair funding for sub-districts. This study recommends revising the regulation to include a mandatory, binding clause and a more equitable funding formula between villages and sub-districts.